Learning to Participate in Politics: Evidence from Jewish Expulsions in Nazi Germany - Mevlude Akbulut-Yuksel; Dozie Okoye; Mutlu Yuksel (Institute of Labor Economics (IZA), 2017)
This paper provides causal evidence on the importance of socioeconomic circumstances, socialization, and childhood events, in the formation of adult political behaviour and attitudes, using region-by-cohort variation in exposure to the Jewish expulsions in Nazi Germany as a quasi-experiment. We find that the expulsion of Jewish professionals had long-lasting detrimental effects on the political attitudes and beliefs of Germans who were at impressionable years during the Nazi Regime. We further demonstrate that these adverse effects on political behaviour and attitudes may be explained by the social changes brought about by the expulsions, which led to relatively lower adult socioeconomic status and civic skills for individuals in their impressionable ages during the expulsions. These results are robust to several alternative specifications, composition bias induced by differential migration and mortality rates across regions and cohorts, and also regional differences in economic performance, wartime destruction, urbanization, and party support, during the Nazi Regime.
Keywords: D72; D74; O12; P16; N40; 330; political behaviour; impressionable years; Jewish expulsions; socioeconomic status